The Molecular Outflow in NGC 253 at a Resolution of Two Parsecs - Krieger Nico; Bolatto Alberto D.; Walter Fabian; Leroy Adam K.; Zschaechner Laura K.; Meier David S.; Ott Jürgen; Weiss Axel; Mills Elisabeth A. C.; Levy Rebecca C.; Veilleux Sylvain; Gorski Mark (IOP, 2022)
We present 0.″15 (̃2.5 pc) resolution ALMA CO(3-2) observations of the starbursting center in NGC 253. Together with archival ALMA CO(1-0) and CO(2-1) data, we decompose the emission into disk and nondisk components. We find ̃7%-16% of the CO luminosity to be associated with the nondisk component (1.2-4.2 × 107 K km s-1 pc2). The total molecular gas mass in the center of NGC 253 is ̃3.6 × 108 M ☉ with ̃0.5 × 108 M ☉ (̃15%) in the nondisk component. These measurements are consistent across independent mass estimates through three CO transitions. The high-resolution CO(3-2) observations allow us to identify the molecular outflow within the nondisk gas. Using a starburst conversion factor, we estimate the deprojected molecular mass outflow rate, kinetic energy, and momentum in the starburst of NGC 253. The deprojected molecular mass outflow rate is in the range of ̃14-39 M ☉ yr-1 with an uncertainty of 0.4 dex. The large spread arises due to different interpretations of the kinematics of the observed gas while the errors are due to unknown geometry. The majority of this outflow rate is contributed by distinct outflows perpendicular to the disk, with a significant contribution by diffuse molecular gas. This results in a mass-loading factor η ={\dot{M}}out}/{\dot{M}}SFR} in the range η ̃ 8-20 for gas ejected out to ̃300 pc. We find the kinetic energy of the outflow to be ̃2.5-4.5 × 1054 erg and a typical error of ̃0.8 dex, which is ̃0.1% of the total or ̃8% of the kinetic energy supplied by the starburst. The outflow momentum is 4.8-8.7 × 108 M ☉ km s-1 (̃0.5 dex error) or ̃2.5%-4% of the kinetic momentum released into the ISM by the feedback. The unknown outflow geometry and launching sites are the primary sources of uncertainty in this study.